Effects of industrial boiling on the nutritional profile of common octopus (Octopus vulgaris) - Oliveira, Helena (2019)
Industrial cooking of common octopus (Octopus vulgaris) under well-established procedures is advantageous for current consumers, which demand healthy and convenient food. This work aimed to evaluate the e ect of industrial water boiling, without the addition of salt, on the nutritional profile of common octopus. True retentions (TRs) were calculated for essential nutrients and toxic elements. After boiling, the moisture content decreased, resulting in a concentration of other constituents (protein, fat, fatty acids, majority of amino acids, phosphorus, zinc, and iodine). High TRs were obtained for some essential nutrients: 90.2% (eicosapentaenoic acid, EPA), 89.1% (docosahexaenoic acid, DHA), 74.6% (indispensable amino acids, IAA), and 86.8% (iodine). In both raw and boiled octopus, polyunsaturated fatty acids (252.2 and 425.1 mg/100 g), leucine (940.1 and 1613.4 mg/100 g), glutamate (1971.5 and 3257.1 mg/100 g), sodium (393.3 and 332.5 mg/100 g), and zinc (12.6 and 16.6 mg/kg) were, respectively, the most abundant fatty acids, IAA, dispensable amino acids, macro, and micro elements. Cadmium, lead, and mercury levels found in boiled octopus were 0.02, 0.10, and 0.08 mg/kg, respectively. The consumption of 150 g (usual portion) of boiled octopus is advisable because it contributes to significant daily intakes of EPA+DHA (>100%), selenium (75.6%), and iodine (12.4%), and 25% of the daily adequate intake of sodium for adults.